Characterization of immune checkpoint inhibitor-associated fulminant type 1 diabetes associated with autoantibody status and ethnic origin - Qiu, Junlin; Luo, Shuoming; Yin, Wenfeng; Guo, Keyu; Xiang, Yufei; Li, Xia; Liu, Zhenqi; Zhou, Zhiguang (Frontiers in Immunology, 2022)
OBJECTIVE: Fulminant type 1 diabetes may uniquely occur as a fatal adverse event during immune checkpoint inhibitor (ICI) therapy. We investigated the clinical and immunological characteristics of ICI-associated fulminant type 1 diabetes (IFD). RESEARCH DESIGN AND METHODS: We enrolled 81 patients with IFD (78 cases from the literature), 57 patients with ICI-associated type 1 diabetes (IT1D) (56 cases from the literature)，45 patients with traditional fulminant type 1 diabetes (TFD), and 43 patients with acute-onset type 1 diabetes for comprehensive analysis including islet autoantibodies and subgroup analysis based on ethnic origin. RESULTS: Patients with IFD accounted for 58.7% (81/138) of patients with ICI-related diabetes. IFD had a more rapid onset than IT1D after ICI therapy (90.5 days vs. 127 days, p <0.05). The onset time and number of infusions after ICI therapy initiation were lower in the antibody-positive IFD group than in the antibody-negative IFD group (both p <0.001). IFD had a more rapid onset and more serious among Caucasians than that among Asians (p <0.05, p <0.01, respectively), and the prevalence of islet autoantibody positivity in the Caucasian IFD were prominently higher than those in the Asian IFD (p <0.05). Onset age and plasma glucose levels were significantly higher in the IFD group than those in the TFD and acute-onset type 1 diabetes groups. HbA1c levels were slightly higher in patients with IFD than those with TFD. CONCLUSIONS: IFD is relatively common in Caucasian population where TFD is very rare or almost absent. IFD occurrence is significantly related to islet autoantibody status and ethnic origin.